The Effect of Providing Lavender Aromatherapy on The Quality of Sleep in The Elderly in Gunamekar Village, Bungbulang District Garut District 2023 - Maryanti, Siti; Silawati, Vivi; Suciawati, Anni (Women, Midwives and Midwifery, 2024)
Background: Old age is a period of decline. This causes a significant decline in cognitive abilities and the speed of the aging process, such as impaired concentration, impaired language and memory abilities. As people get older, many changes occur, both physically and mentally. Changes in appearance that are part of the normal aging process, such as decreased vision, lack of sleep or decreased stamina, pose a threat to the integrity of the elderly. Objective: Analyze the effect of giving Lavender Aromatherapy on the Sleep Quality of the Elderly in Gunamekar Village, Bungbulang District, Garut Regency in 2023 Methodology: The research design used was quasi experimental with pre and post two group design. The sample in this study consisted of 32 pregnant women, consisting of 16 people in the intervention group and 16 people in the control group. The sampling technique uses random sampling technique. The research instrument used was the Pittsburgh Sleep Quality Index (PSQI) questionnaire regarding sleep quality. Data were analyzed using descriptive statistics and the Wiolcoxon test to determine the difference in sleep quality scores before and after the intervention group and the control group Research Results: showed changes in the sleep quality of elderly women before and after giving lavender aromatherapy. The results of statistical knowledge tests showed that the significance value (p-value) was 0.000. The p-value (0.000) < p alpha (0.05) means that there is an effect of giving lavender aromatherapy on the sleep quality of elderly women in Gunamekar Village, Bungbulang District, Garut District in 2023. Conclusion: giving lavender aromatherapy provides significant changes to the sleep quality of elderly women Suggestion: It is hoped that the elderly, their families and the community can play an active role in health service programs, especially regarding the health of the elderly, to be able to carry out routine checks so that they can treat their complaints as early as possible